2019
DOI: 10.3382/ps/pey434
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diets with different energy and bile acids levels on growth performance and lipid metabolism in broilers

Abstract: This experiment was conducted to evaluate the effects of bile acids (BAs) on the growth performance and lipid metabolism of broilers fed with different energy level diets. 480 one-day-old Arbor Acres broilers (45.01 ± 0.26 g) were allotted to a 2 × 2 factorial design with 2 levels of energy (basal or high-energy level) and 2 levels of BAs (with or without BAs supplementation), resulting in 4 groups of 8 replicates; the experiment lasted 42 d. High-energy diets decreased the feed/gain ratio (F/G) from 1 to 21 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
50
2
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 56 publications
13
50
2
2
Order By: Relevance
“…Body weight gain was not changed by the supplementation of bile acids and lipase alone or in combination in LE diet during starter, finisher and the overall period. However, BW gain was more in LE diet compared to HE diet in starter and the overall period which is contrary to the findings of the previous researcher who reported that feeding low-energy diets reduced BW gain compared to highenergy diets during 14 d period (Zhao and Kim, 2017;Hu et al, 2018) and during the period of 28 to 35 d (Ge et al, 2018). In birds offered reduced energy diets, they probably compensated for lower energy intake per kilogram of feed.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Body weight gain was not changed by the supplementation of bile acids and lipase alone or in combination in LE diet during starter, finisher and the overall period. However, BW gain was more in LE diet compared to HE diet in starter and the overall period which is contrary to the findings of the previous researcher who reported that feeding low-energy diets reduced BW gain compared to highenergy diets during 14 d period (Zhao and Kim, 2017;Hu et al, 2018) and during the period of 28 to 35 d (Ge et al, 2018). In birds offered reduced energy diets, they probably compensated for lower energy intake per kilogram of feed.…”
Section: Discussioncontrasting
confidence: 88%
“…Similarly, supplementation of bile acid and lipase alone or in combination in LE diet also did not affect relative organ weight and breast muscle yield of broilers. Similar organ weight and breast muscle yield of broilers in LE and HE diet are in agreement with the findings of Ge et al (2018) and Upadhaya et al (2019a) who reported that LE diet had no effect on liver, spleen, gizzard, abdominal fat, bursa of fabricius and breast muscle weight. Additionally, similar results were also reported by Corduk et al (2007) and Rabie et al (2010) who stated that carcass traits of broiler chicks remained unaffected by dietary energy level.…”
Section: Effects Of Bile Acids and Lipase Supplementation In Low-enersupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies have revealed that BW gain and feed efficiency were decreased by feeding low-energy diets, while feed intake was not affected (2,3) . This is similar to our finding that the ADG was lower and FCR was higher in the low-ME groups than the normal ME groups, which may be due to the fact that dietary energy being more easily utilised for chicken growth.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolisable energy (ME) in the diet is a critical factor that greatly influences the intake of all other nutrients in the poultry species (1) . Moreover, the feed efficiency, growth performance and body composition of broiler chickens are likely to be influenced by the ME intake (2,3) . It was commonly believed that the high-ME diet for broiler chickens is produced by the addition of lipids (fats and oils) because lipids have the highest energy value compared with other nutrients (4) .…”
mentioning
confidence: 99%